Union Minière du Haut-Katanga 1906-1956 : évolution des techniques et des activités sociales. (Bruxelles : L. Cuypers, 1957)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: mijnindustrie; Belgisch Congo